2020
DOI: 10.1177/0963689720926157
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing of Human Peripheral Nerve in Response to Injury: Distinctive Analysis of the Nerve Repair Pathways

Abstract: The development of regenerative therapies for central nervous system diseases can likely benefit from an understanding of the peripheral nervous system repair process, particularly in identifying potential gene pathways involved in human nerve repair. This study employed RNA sequencing (RNA-seq) technology to analyze the whole transcriptome profile of the human peripheral nerve in response to an injury. The distal sural nerve was exposed, completely transected, and a 1 to 2 cm section of nerve fascicles was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 49 publications
5
47
2
Order By: Relevance
“…The cells then upregulate and release a whole host of neurotrophic and cell survival factors, including glial-derived neurotrophic factor (GDNF) [ 15 ], nerve growth factor (NGF) [ 16 , 17 ], brain-derived neurotrophic factor (BDNF) [ 18 ], and nuclear factor erythroid 2-related factor (Nrf2) in animal models. Our RNA Seq analyses support that the human sural nerve tissues that we implanted show similarities to the repair phenotype in animal models [ 19 ]. Our strategy is to use APNG to implant a living repair system with growth factors to reduce cell death of dopamine-producing neurons and aid in the long-term maintenance of motor function, including gait and balance.…”
Section: Introductionsupporting
confidence: 64%
“…The cells then upregulate and release a whole host of neurotrophic and cell survival factors, including glial-derived neurotrophic factor (GDNF) [ 15 ], nerve growth factor (NGF) [ 16 , 17 ], brain-derived neurotrophic factor (BDNF) [ 18 ], and nuclear factor erythroid 2-related factor (Nrf2) in animal models. Our RNA Seq analyses support that the human sural nerve tissues that we implanted show similarities to the repair phenotype in animal models [ 19 ]. Our strategy is to use APNG to implant a living repair system with growth factors to reduce cell death of dopamine-producing neurons and aid in the long-term maintenance of motor function, including gait and balance.…”
Section: Introductionsupporting
confidence: 64%
“…After nerve injury, gene expression in SCs is dramatically changed. Hundreds of genes involved in cell cycle, cell proliferation, immune cell function, synaptic structure and neuron function, among others, are differentially regulated after axotomy [ 8 , 10 , 11 , 12 ]. Interestingly, additional to the neurotrophic factor expression, SCs from the muscle and cutaneous branches of the femoral nerve also show several other genes with different expression patterns.…”
Section: Motor and Sensory Schwann Cellsmentioning
confidence: 99%
“…Many genes related to cell growth, response to external stimuli and neuritogenesis are regulated similarly to immature SCs, reactivating developmental mechanisms. However, an injury-specific program is activated as well, involving also up- or down- regulation of genes related to signal transduction, cell death, immune response, transcriptional regulation, protein transport and metabolism, among others [ 10 , 11 , 12 ]. The loss of axonal contact also triggers denervated SCs to transiently express NRG1 type I as an autocrine signal to promote SC differentiation and remyelination [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that SCs upregulated the expression of genes related to dedifferentiation, immunity, and growth, such as IL-6, IL-10, leukemia inhibitory factor (LIF), and glial cellderived neurotrophic factor (GDNF) significantly increased FIGURE 1 | Graphical illustration of PNS involving the pathology, diagnosis, treatment, therapeutic mechanism and safety of clinical application in PD. (Welleford et al, 2020). Collectively, the evidence indicates that SCs are involved in PD neuroinflammation.…”
Section: Pathologic Changes In the Pns In Pdmentioning
confidence: 95%